How do you choose and how well does it work?: the selection and effectiveness of emotion regulation strategies and their relationship with borderline personality disorder feature severity. Issue 3 (3rd April 2018) - Kuo, Janice R.; Fitzpatrick, Skye; Krantz, Lillian H.; Zeifman, Richard J.
ABSTRACT: There is little research examining whether the selection of emotion regulation strategies is compromised among individuals characterised by emotion dysregulation. In a sample of 149 undergraduates, we examined the selection and effectiveness of 2 emotion regulation strategies ( reappraisal or distraction ) in response to emotionally evocative stimuli, and their relationship with emotion dysregulation, measured by borderline personality disorder (BPD) feature severity. Stimulus intensity and self-reported negative emotional intensity were also compared as predictors of strategy selection. Results indicated that self-reported negative emotional intensity was a stronger predictor of strategy selection than stimulus intensity, and participants generally selected reappraisal over distraction. However, increases in self-reported negative emotional intensity was associated with an increased likelihood of choosing distraction, particularly among individuals higher in BPD features. In general, distraction exhibited less effectiveness than reappraisal, and higher BPD features did not differentially impact such effectiveness. Our findings indicate that individuals higher in emotion dysregulation prefer to use distraction as self-reported negative emotional intensity increases, a strategy which, overall, may not be as effective as reappraisal. Selection, rather than effectiveness of emotion regulation strategy might be a key feature of individuals characterised by emotion dysregulation.